The student as interpreter of the digital age: Emerging meanings in the educational use of artificial intelligence at a public university in Argentina - Gilardoni, Fabiana (2026)
The growing use of artificial intelligence (AI) in higher education raises pedagogical, ethical, and formative questions that need to be understood from students’ own experiences and perceptions. The aim was to interpret the meanings that university students construct regarding their active role in the educational use of artificial intelligence in the digital era. Using a qualitative approach, a hermeneutic phenomenological design was adopted, drawing on six in-depth interviews and one focus group with four participants, conducted with advanced students from the Special Education teacher-training program at the National University of Misiones, selected through purposive sampling. A semi-structured interview guide was used, and the analysis was carried out through an interpretive thematic categorization process. The results show that AI is understood as a tool that mediates learning rather than as a substitute for human reasoning. In their accounts, participants tend to describe reflective and metacognitive practices, as well as self-regulation strategies, which strengthen their agency and intellectual autonomy in the learning process. Likewise, ethical concerns related to authorship, academic honesty, and the risk of technological dependence are interpreted, along with the expressed need for institutional guidance and spaces for ethical training. In conclusion, these meanings suggest the advisability of integrating AI through humanistic pedagogical approaches aimed at promoting critical thinking, ethical responsibility, and active learning, recognizing students as reflective subjects capable of constructing meaning in complex digital environments.